FIND THE INDICATED POWER OF A COMPLEX NUMBER

How to find the indicated power of a complex number :

We are using the De Moivre's theorem, to find the indicated power of a complex number.

Definition of De Moivre's theorem :

De Moivre's theorem states that the power of a complex number in polar form is equal to raising the modulus to the same power and multiplying the argument by the same power.

Let z  =  r(cos θ + i sin θ) be a polar form of a complex number.

According to De Moivre's theorem, 

zn  =  [r(cos θ + i sin θ)]n

z=  rn(cos nθ + i sin nθ)

For all positive integers n.

Example 1 :

(cos π/4 + i sin π/4)3

Solution :

Given, z3  =  (cos π/4 + i sin π/4)3

Using the De Moivre's formula :

zn  =  rn(cos nθ + i sin nθ )

Here n  =  3, r  =  1 and θ  =  π/4

z3  =  13(cos 3π/4 + i sin 3π/4)

z3  =  1(cos 3π/4 + i sin 3π/4)

By using the calculator, we get

z3  =  -√2/2 + i √2/2

Example 2 :

[3(cos 3π/2 + i sin 3π/2)]5

Solution :

Given, z5  =  [3(cos 3π/2 + i sin 3π/2)]5

Using the De Moivre's formula :

zn  =  rn(cos nθ + i sin nθ )

Here n  =  5, r  =  3 and θ  =  3π/2

z5  =  35(cos 15π/2 + i sin 15π/2)

By using the calculator, we get

z=  243(0 - i)

z5  =  243i

Example 3 :

[2(cos 3π/4 + i sin 3π/4)]3

Solution :

Given, z3  =  [2(cos 3π/4 + i sin 3π/4)]3

Using the De Moivre's formula :

zn  =  rn(cos nθ + i sin nθ )

Here n  =  3, r  =  2 and θ  =  3π/4

z3  =  23(cos 9π/4 + i sin 9π/4)

By using the calculator, we get

z3  =  8(√2/2 + i √2/2)

z3  =  [(8√2/2) + (i 8√2/2)]

z3  =  4√2 + i 4√2

Example 4 :

(1 + i)5

Solution :

Given, standard form z  =  (1 + i)

The polar form of the complex number z is

(1 + i)  =  r cos θ + i sin θ ----(1)  

Finding r :

r  =  √[(1)2 + (1)2]

r  =  √2

Finding α :

α  =  tan-1(1/1)

α  =  π/4

Since the complex number 1 + i is positive, z lies in the first quadrant.

So, the principal value θ  =  π/4

By applying the value of r and θ in equation (1), we get

1 + i  =  √2(cos π/4 + i sin π/4)

So, the polar form of z is √2(cos π/4 + i sin π/4)

Then,

z=  [√2(cos π/4 + i sin π/4)]5

Using the De Moivre's formula :

zn  =  rn(cos nθ + i sin nθ )

Here n  =  5, r  =  √2 and θ  =  π/4

z5  =  (√2)5(cos 5. π/4 + i sin 5 . π/4)

z5  =  4√2(cos 5π/4 + i sin 5π/4)

By using the calculator, we get

z5  =   4√2(-√2/2 - i √2/2)

z5  =  [-( 4√2 . √2/2) - (i  4√2. 8√2/2)]

z5  =  -4 - 4i

Example 5 :

(1 - √3i)3

Solution :

Given, standard form z  =  (1 - √3i)

The polar form of the complex number z is

1 - √3i  =  r cos θ + i sin θ ----(1)  

Finding r :

r  =  √[(1)+ (√3)2]

r  =  2

Finding α :

α  =  tan-1(√3/1)

α  =  π/3

Since the complex number 1 - √3i is positive and negative, z lies in the fourth quadrant.

So, the principal value θ  =  -π/3

By applying the value of r and θ in equation (1), we get

1 - √3i  =  2(cos -π/3 + i sin -π/3)

So, the polar form of z is 2(cos -π/3 + i sin -π/3)

Then,

z=  [2(cos -π/3 + i sin -π/3)]3

Using the De Moivre's formula :

zn  =  rn(cos nθ + i sin nθ )

Here n  =  3, r  =  and θ  =  -π/3

z3  =  (2)3[cos (-3π/3) + i sin (-3π/3)]

z3  =  8[cos (-3π/3) + i sin (-3π/3)]

By using the calculator, we get

z3  =   8(-1 - i0)

z3  =  -8

Example 6 :

(-1 - 6i)3

Solution :

Given, standard form z  =  (-1 - 6i)3

Comparing with (a - b)3, we get a3 - 3a2b + 3ab2 - b3

a = -1 and b = 6i

= (-1)3 - 3(-1)2(6i) + 3(-1)(6i)2 - (6i)3

= -1 - 18i - 3(36i2) - 216i3

= -1 - 18i - 3(36(-1)) - 216i2 i

= -1 - 18i + 108 - 216(-1) i

= -1 - 18i + 108 + 216i

= 107 + 198i

Example 6 :

(3 – 2i)(5 + 4i) – (3 – 4i)2

Solution :

(3 – 2i)(5 + 4i) – (3 – 4i)2

(3 – 2i)(5 + 4i) = 3(5) + 3(4i) + (-2i)(5) - 2i(4i)

= 15 + 12i - 10i - 8i2

= 15 + 2i - 8(-1)

= 15 + 2i + 8

= 23 + 2i

Example 7 :

(1 - 2i)2 (1 + 2i)2

Solution :

(1 - 2i)2 - (1 + 2i)2

(a - b)2 = a2 - 2ab + b2

(1 + 2i)2 = 12 - 2(1)(2i) + (2i)2

= 1 - 4i + 4i2

= 1 - 4i - 4

= -3 - 4i

(1 + 2i)2 = 12 + 2(1)(2i) + (2i)2

= 1 + 4i + 4i2

= 1 + 4i - 4

= -3 + 4i

(1 - 2i)2 - (1 + 2i)2 = -3 - 4i - (-3 + 4i)

= -3 - 4i + 3 - 4i

= -8i

(1 - 2i)2 - (1 + 2i)2 = -8i

Example 7 :

(2 + 3i)2 (2 - 3i)2

Solution :

(2 + 3i)2 - (2 - 3i)2

(a - b)2 = a2 - 2ab + b2

(2 + 3i)2 = 22 + 2(2)(3i) + (3i)2

= 4 + 12i + 9i2

= 4 + 12i - 9

= -5 + 12i

(2 - 3i)2 = 22 - 2(2)(3i) + (3i)2

= 4 - 12i + 9i2

= 4 - 12i - 9

= -5 - 12i

(2 + 3i)2 - (2 - 3i)2 = -5 + 12i - (-5 - 12i)

-5 + 12i + 5 + 12i

= 24i

(2 + 3i)2 - (2 - 3i)2 = 24i

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Pascal Triangle and Binomial Expansion

    Feb 01, 25 10:12 AM

    pascaltriangle1.png
    Pascal Triangle and Binomial Expansion - Concept - Examples

    Read More

  2. SAT Math Resources (Videos, Concepts, Worksheets and More)

    Feb 01, 25 06:26 AM

    SAT Math Resources (Videos, Concepts, Worksheets and More)

    Read More

  3. Digital SAT Math Problems and Solutions (Part - 106)

    Feb 01, 25 06:23 AM

    digitalsatmath107.png
    Digital SAT Math Problems and Solutions (Part - 106)

    Read More